Tantangan implementasi SAK EMKM pada UMKM di Kalimantan Barat: Kajian literatur - Sihombing, Fransisca Marito; Mare, Rita Nian Jubata (Nur Science Institute, 2025)
This study examines the challenges in implementing Financial Accounting Standards for Micro, Small, and Medium Enterprises (SAK EMKM) among MSMEs in West Kalimantan using a systematic narrative literature review method. The research systematically analyzes peer-reviewed journals, research reports, and relevant publications from academic databases to identify implementation barriers specific to the border region context. The main challenges identified include limited accounting knowledge among MSME owners, perceived complexity of standards, human resource and financial constraints, inadequate information technology infrastructure, and insufficient ecosystem support. The geographical characteristics of West Kalimantan, as a border region, combined with educational disparities and infrastructure limitations, create unique implementation barriers that have not been extensively addressed in previous studies. This study contributes to the literature by providing the first comprehensive analysis of SAK EMKM implementation challenges in Indonesia’s border regions, offering contextual insights for the development of targeted intervention strategies. The findings recommend collaborative approaches involving multi-stakeholder partnerships in education, training, and infrastructure development, tailored to local contexts, to ensure the relevance and sustainability of implementation.